IJDAR 2020
DOI: 10.4192/1577-8517-v20_4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Automation Potentials of Management Reporting Processes

Abstract: Digitalization is driving the automation of accounting processes. It is estimated that up to 70% of administrative activities could be carried out by automated, i.e. rule-based sequences, which promises a considerable increase in productivity and efficiency for repetitive, standardized processes. In recent years, Robotic Process Automation (RPA) has been increasingly and successfully used for such purposes. However, before implementing a RPA solution, it is essential to evaluate the automation potentials. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Periodic closure and statement reporting involve coordinating and verifying extensive data from numerous entities; spreadsheets, tables, and lists of records are used to ensure that information is accurate, complete, and current (Kaya et al 2019). In this regard, Matthies (2020) recommends the assessment of automation potential for management‐reporting processes in a manner aligned with cost‐benefit analysis. Taking a more holistic approach, Zhang (2019) examines the use of RPA for the whole accounting activity of an energy company, considering all its constituents: bookkeeping, management accounting, financial accounting, and reports to third parties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodic closure and statement reporting involve coordinating and verifying extensive data from numerous entities; spreadsheets, tables, and lists of records are used to ensure that information is accurate, complete, and current (Kaya et al 2019). In this regard, Matthies (2020) recommends the assessment of automation potential for management‐reporting processes in a manner aligned with cost‐benefit analysis. Taking a more holistic approach, Zhang (2019) examines the use of RPA for the whole accounting activity of an energy company, considering all its constituents: bookkeeping, management accounting, financial accounting, and reports to third parties.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, more attention should be paid to aspects such as costs of implementation versus expected prior‐implementation savings in the short or medium term; the frequency and volume of tasks to be automated and the costs to automate them; and the calculation of investment amortization. The number of processes required to achieve complete amortization is determined by dividing the RPA installation costs by the cost‐saving potential of each automated process (i.e., current cost per process, cost per automated process) (Matthies 2020).…”
Section: New Avenues Of Researchmentioning
confidence: 99%
“…The study illustrates how RPA can significantly increase productivity and efficiency for repetitive and standardized processes. By evaluating automation potentials, Matthies (2020) demonstrates that RPA can lead to considerable time savings and cost benefits, making a compelling case for the adoption of automation in accounting practices.…”
Section: Impact Of Automation On Time Management and Productivitymentioning
confidence: 99%
“…It was stated that blockchain appears to be the tools for the auditors to provide the assurance that is required by the clients. Matthies (2020), in his study on assessing the automation potentials of management reporting processes, revealed that the cost saving potentials on the one hand and the amortization of implementation costs on the other hand help the assessment of cost-based evaluation of automation projects. Consideration must be given to the implementation of new technology whether it is profitable to the company both in the short term and long term.…”
Section: Empirical Studiesmentioning
confidence: 99%